Violência psicológica e verdade jurídica: como é construída a verdade jurídica sobre a violência psicológica contra a mulher pelos agentes do sistema de justiça criminal - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The term gender as it is used today has undergone numerous changes in its concept, from the initial idea of ​​dissociation from the binary biological view, to a historical and cultural construction of the social roles of each individual in society. Today it is seen as a category of analysis, along with other variables such as social class and race. The social structure has been shaped by gender, especially the machismo and patriarchy that sustain male domination and order, through the symbolism by which they are perpetuated. With the objective of giving visibility to women, in a positive way, and seeking to conquer their rights, the feminist struggle began. In the same sense, by uniting critical theory and feminist criminology, the scholars worked for the insertion of feminist studies within history, sociology, criminology itself and other areas of knowledge. In addition to conquering rights for women, hostages of the sexual division, the scope of the battles was to introduce the female issue as an integral part of society, as well as in the criminal issue, both as an agent and as a victim. In both situations, women are doubly penalized in the criminal justice system, which is also unequal. One of the main consequences of the gender hierarchy is violence, an evil that affects most women in the system of domination-exploitation to which they are subjected Violence is represented in the most varied ways, but it has a silent way and with glaring and eternal consequences, the psychological one, which begins subtly and silently and, in most cases, opens doors to others. However, even with an absurd number of occurrences, those that actually reach the judiciary are few; those who receive the attention and care they need are even fewer. This is how the legal truth is presented, Mills' concept that portrays a vocabulary of motives that is built by criminal justice agents about which truth is interesting and safe, meeting social expectations. Thus, for the construction of the present work and in order to understand the legal truth produced about psychological violence against women, an analysis of 100 (one hundred) cases pending in the Criminal Court of Santana do Livramento between the period 2020 to 2022 The results of the analysis led to the discovery that the form of production of legal truth in the analyzed cases was carried out in such a way as to exclude cases of psychological violence or to reduce their importance, failing to protect them when not accompanied by evidence considered sufficient. Thus, despite the crime of psychological violence against women being typified, its application is not carried out, failing to materialize the protection guaranteed to women, especially in the Maria da Penha Law.
Psychological violence and legal truth: how the legal truth about psychological violence against women by agents of the criminal justice system is constructed
Keywords: Gênero; Criminologia crítica feminista; Violência psicológica contra a mulher; Verdade jurídica; Genre; Feminist critical criminology; Psychological violence against women; Legal truth; CNPQ::CIENCIAS SOCIAIS APLICADAS